1924 - Delenda São Paulo: a cidade e a população vítimas das armas de guerra e das disputas políticas - Assunção Filho, Francisco Moacir (2014)
The research deals with the Paulista Revolt July 5, 1924 , known as the second lieutenants revolt that took place in São Paulo , between the 5th and 28th of July of that year , leaving a balance of 503 dead and 4,846 wounded , according to officers. The study, which draws on the lessons of historians Edward P. Thompson and Carlo Ginzburg, aimed to rescue the stories of ordinary people who lived through the conflict and were among its main victims, despite not belonging to either of the two warring sides - the rebels, who took the city, and legal forces that bombed to retake it. These fellows, residents of the neighborhoods most affected in the conflict, as Mooca, Bras and Ipiranga, are almost forgotten in short bibliography and in theses and dissertations dealing with the matter. Thus, rescuing his career from traces such as letters, newspaper reports, accounts and photographs can collaborate to bring new perspectives on the topic Uprising Lieutenants, 1924 understudied in Brazilian historiography and even in the state. In the research, worked with books of memoirs and chroniclers, the big news of the working press and press photos of the conflict, letters, memorials and archives materials throughout Brazil. Classic works on the subject were also used. The main topic was the participation of civilians in the conflict , their suffering , the horror of the bombing and their strategies for survival in the face of a civil war on at the time , second most important city in Brazil , after the federal capital , Rio January . We worked in the same way, with criticism of opponents and the justifications for the bombing of situationists the state capital and the identification of weapons of war used in the comparison, both legal, as the rebel. At the same time, the research sought to put into perspective the facts, highlighting the rise even before the New State, strong authoritarian tendencies in the Brazilian State, during the government of Arthur Bernardes and his successor, Washington Luiz , mainly geared to repression anarchists , rebels and transgressors of the order in general workers . The exodus of the population during the conflict - have left the city on the run about 250 thousand people, according to the City - and the looting caused by famine and shortages were other themes addressed in research